Hepatic angiosarcomatous transformation of a mediastinal germinal cell tumor: A care case report. Issue 51 (December 2017) - Corrias, Giuseppe; Escalon, Joanna G.; Tang, Laura; Monti, Serena; Saba, Luca; Mannelli, Lorenzo
Abstract: Rationale: Mediastinal nonseminomatous germ cell tumor (NSGCT) is an uncommon entity. Metastatic hepatic sarcomatous transformation is rare. Patient concerns: We report a 24-year-old man with no previous related medical history presented with chest pain and left arm numbness. Diagnoses: The x-ray showed an anterior mediastinal mass. The chest computed tomography (CT) confirmed the presence of a mildly enhancing mass in the same location, without invasion of any vascular structure. A CT-guided biopsy was performed, revealing a primary mediastinal nonseminomatous germ cell tumor (NSGCT), yolk sac histology, with areas of somatic transformation to malignant nerve sheath tumor. After surgery patient was followed-up with imaging. Two years later a CT scan showed a new hepatic hyper vascular lesion, confirmed by a subsequent magnetic resonance imaging (MRI) and positron emission tomography (PET) scan. A CT-guided biopsy revealed a hepatic metastatic transformation to angiosarcoma of the primitive NSGCT. Interventions: The patient went on to received palliative chemotherapy. Outcomes: The patient is being followed-up regularly at the outpatient department. Lessons: Because of the potential of metastatic sarcoma arising from germ cell tumors, these patients should undergo periodical follow-up, with periodical scans. PETscan might have a role in the follow-up of these patients.